Serious videogames for teaching recycling based on the STEM Project - Chacon-Castro M.; Lopez-Quintero J.; Acosta-Vargas P.; Luna-Pineda J.; Jadán Guerrero, Janio (My University, 2022)
This article shows an educational practice laboratory, where high school students created educational video games for teaching recycling. This allows the formation of the STEM research with guidance of the researcher. This project had a great impact for the educational institution and for the students presenting this project at the I International Congress of Steam and Active Methodologies (2021). The objective of this research is to design and evaluate serious video games for teaching recycling based on the STEM methodology (Science, Technology, Engineering and Mathematics). The strategy in this research is: planning, observation, action and reflection. The video game programming is done in the Scratch application where students program the code through blocks. This educational project was applied to 40 sophomore high school students from a private institution. Among the results it is found that there is evidence of a motivational increase on part of the students in mathematics class, due to the fact that when programming in blocks they are more active, dynamic and playful during the learning process. © 2022 IEEE.
Keywords: Adaptive learning; Asynchronous; Combined operations; Mathematics; methodological strategy